Pendampingan Penggunaan Pengusulan Jenjang Jabatan Akademik Dosen menggunakan Aplikasi Sikito - Puji Astuti Puji; Susmita Susmita (Pusat Studi Teknologi Informasi Fakultas Ilmu Komputer Universitas Bandar Lampung, 2022)
The development of the stages of promotion of functional positions of lecturers includes certification, development of professional competencies through further studies, promotion of academic positions and the development of scientific papers, research or scientific publications. So it is important to provide training that can provide understanding for lecturers in the environment of the Bina Husada College of Health Sciences (STIK) in proposing an increase in the level of academic positions, namely through the SIKITO application. The results of the participants' proposals with guidance and assistance through training on the use of the cycloto application from 4 (four) lecturers have received the JJA Lektor Decree and 2 (two) lecturers are in the JJA proposal to the Head Lector, and there are 14 (fourteen) lecturers in the process of verifying files and assessing credit numbers by the JJA LLDIKTI 2 team.